The First case of Locally Acquired Tick-Borne Babesia Microti Infection in Canada - Jared MP Bullard; Arshad N Ahsanuddin; Anamarija M Perry; L Robbin Lindsay; Mahmood Iranpour; Antonia Dibernardo; Paul G Van Caeseele (Canadian Journal of Infectious Diseases and Medical Microbiology)
A child with a complicated medical history that included asplenia acquired an infection with Babesia microti in the summer of 2013 and had not travelled outside of Manitoba. Although the clinical findings were subtle, astute laboratory work helped to reach a preliminary identification of Babesia species, while reference laboratory testing confirmed the diagnosis. Blacklegged ticks (Ixodes scapularis) are known to transmit Borrelia burgdorferi and Anaplasma phagocytophilum in the province; however, the present case represents the first known instance of tick-borne B microti, both in Manitoba and in Canada. The expanding territory of the blacklegged tick increases the relevance of this emerging infection. Clinicians, laboratory medical practitioners and public health officials should be aware of B microti as a potential locally acquired infection in Canada.